Radiation-Induced Graft Copolymerization of Methacrylonitrile onto Poly (Tetrafluoroethylene-co-ethylene) Film by Discontinuous Method - Thakur, R. K.; Kaur, I.; Singh, M.; Kumar, N. (Journal of Scientific Research, 2023)
An attempt has been made to graft copolymerize the vinyl monomer methacrylonitrile onto poly tetrafluoroethylene-co-ethylene, known as Tefzel film, by the double-irradiation method in aqueous medium. Optimum conditions for attaining the maximum percentage of grafting were evaluated. The maximum percentage of grafting for methacrylonitrile was obtained 128.7 % at an optimum dose of 24.9 kGy using 2.98 mol L-1 of methacrylonitrile. Investigations on the effects of different chain-length aliphatic alcohols, methanol, ethanol, n-butanol, cyclohexanol and amyl alcohol on the grafting percentages of methacrylonitrile have been performed. Characterization of Tefzel and grafted Tefzel films have been performed by infrared spectroscopy and Thermogravimetric Analysis. Methacrylonitrile grafted Tefzel films showed better thermal stability.